Cobalt Complexes with Pyrazole Ligands as Catalyst Precursors for the Peroxidative Oxidation of Cyclohexane: X‐ray Absorption Spectroscopy Studies and Biological Applications. Issue 4 (30th January 2014) - F. S. Silva, Telma; M. D. R. S. Martins, Luísa; Guedes da Silva, M. Fátima C.; Kuznetsov, Maxim L.; Fernandes, Alexandra R.; Silva, Ana; Pan, Chun‐Jern; Lee, Jyh‐Fu; Hwang, Bing‐Joe; J. L. Pombeiro, Armando
Abstract [CoCl(μ‐Cl)(HpzPh)3]2 (1) and [CoCl2(HpzPh)4] (2) were obtained by reaction of CoCl2 with HC(pzPh)3 and HpzPh, respectively (HpzPh=3‐phenylpyrazole). The compounds were isolated as air‐stable solids and fully characterized by IR and far‐IR spectroscopy, MS(ESI+/−), elemental analysis, cyclic voltammetry (CV), controlled potential electrolysis, and single‐crystal X‐ray diffraction. Electrochemical studies showed that 1 and 2 undergo single‐electron irreversible CoII→CoIII oxidations and CoII→CoI reductions at potentials measured by CV, which also allowed, in the case of dinuclear complex 1, the detection of electronic communication between the Co centers through the chloride bridging ligands. The electrochemical behavior of models of 1 and 2 were also investigated by density functional theory (DFT) methods, which indicated that the vertical oxidation of 1 and 2 (that before structural relaxation) affects mostly the chloride and pyrazolyl ligands, whereas adiabatic oxidation (that after the geometry relaxation) and reduction are mostly metal centered. Compounds 1 and 2 and, for comparative purposes, other related scorpionate and pyrazole cobalt complexes, exhibit catalytic activity for the peroxidative oxidation of cyclohexane to cyclohexanol and cyclohexanone under mild conditions (room temperature, aqueous H2O2). In situ X‐ray absorption spectroscopy studies indicated that the species derived from complexes 1 and 2 during the oxidation of cyclohexane (i.e., Ox‐1 and Ox‐2, respectively) are analogous and contain a CoIII site. Complex 2 showed low in vitro cytotoxicity toward the HCT116 colorectal carcinoma and MCF7 breast adenocarcinoma cell lines.